2021
DOI: 10.3390/genes12121914
|View full text |Cite
|
Sign up to set email alerts
|

TNFA and IL10 Polymorphisms and IL-6 and IL-10 Levels Influence Disease Severity in Influenza A(H1N1)pdm09 Virus Infected Patients

Abstract: Cytokines are key modulators of immune response, and dysregulated production of proinflammatory and anti-inflammatory cytokines contributes to the pathogenesis of influenza A(H1N1)pdm09 virus infection. Cytokine production is impacted by single nucleotide polymorphisms (SNPs) in the genes coding for them. In the present study, SNPs in the IL6, TNFA, IFNG, IL17A, IL10, and TGFB were investigated for their association with disease severity and fatality in influenza A(H1N1)pdm09-affected patients with mild diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…In the center of the cytokine storm is a classic pro-inflammatory factor called tumor necrosis factor-α (TNF-α), and a crucial component of the inflammatory response is interleukin-6 (interleukin −6, IL-6) ( Hirano, 2021 ; Pandey and Karupiah, 2022 ). The influenza virus infection can cause many organ lesions, even death, by upregulating the levels of TNF-α, IL-6, and other inflammatory cytokines and inducing a strong pro-inflammatory immune response ( Alagarasu et al, 2021 ). Secretory IgA (sIgA) is the antibody with the highest proportion at mucosal sites and has a stronger antiviral neutralizing capacity ( Berthold and Wormald, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the center of the cytokine storm is a classic pro-inflammatory factor called tumor necrosis factor-α (TNF-α), and a crucial component of the inflammatory response is interleukin-6 (interleukin −6, IL-6) ( Hirano, 2021 ; Pandey and Karupiah, 2022 ). The influenza virus infection can cause many organ lesions, even death, by upregulating the levels of TNF-α, IL-6, and other inflammatory cytokines and inducing a strong pro-inflammatory immune response ( Alagarasu et al, 2021 ). Secretory IgA (sIgA) is the antibody with the highest proportion at mucosal sites and has a stronger antiviral neutralizing capacity ( Berthold and Wormald, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, we found that DEGs were enriched in TNF signaling pathways, suggesting that TNF is an important indicator of H1N1 infection. Multiple meta-analyses have also revealed that TNF gene polymorphisms are associated with H1N1 virus susceptibility and severity of infection [22][23][24][25][26]. On the other hand, no elevated levels of TNFrelated factors were detected in the plasma of pregnant women vaccinated against the H1N1 virus.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TLR4 or CD14 may bind to ssRNA, activating MyD88, and then the activation of MyD88 transmitting signals and activating NF-κB p65, which increases the production of proinflammatory cytokines of IFN-γ, IL-6, and chemokines of MCP-1, MIP-1α, and IP-10, while inhibiting the production of anti-inflammatory cytokine of IL-10 ( Zhu et al, 2018 ; Ma et al, 2020 ). Besides, clinical research has shown that the levels of cytokines IL-6 and IL-17 are related to the disease severity of H1N1 infection patients, especially the IL-6 may be a biomarker for predicting fatal outcomes of H1N1 infection ( Alagarasu et al, 2021 ). Hypoxia-inducible factor 1α (HIF-1α) is an important transcription factor that regulates many downstream target genes ( Huang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%